Effect of Calcium Addition on Extracellular Enzymes and Soil Organic Carbon in Maize Rhizosphere Soils - Zhaoquan He; Xue Shang; Xiaoze Jin (Agronomy)
This study examined the regulatory mechanism of calcium (Ca) amendment on the dynamics of soil organic carbon (SOC) fractions and extracellular enzyme activities, elucidating the role of Ca in soil carbon cycling processes. A field experiment with maize was conducted, comparing treatments of low calcium (T1), high calcium (T2), and a calcium-free control (CK). Measurements included inter-root SOC fractions—soluble organic carbon (DOC), microbial biomass carbon (MBC), and readily oxidizable organic carbon (ROC)—and the activities of the following extracellular enzymes: β-xylanase, β-glucosidase (β-glu), phenol oxidase (Phox), peroxidase (Pero), phosphatase (Phos), acetylaminoglucosidase (NAG), and urease. The main findings indicated the following: (1) Calcium addition significantly increased SOC content (115.04% and 99.22% higher in T1 and T2, respectively, than CK during the entire reproductive period) and enhanced microbial activity (elevated DOC and MBC). However, SOC decreased by 8.44% (T1) and 16.38% (T2) relative to CK in the late reproductive stage (irrigation–ripening), potentially reflecting microbial utilization (supported by the inverse correlation between SOC and MBC/DOC), and maize carbon reallocation during grain filling. (2) Calcium activated β-glu, Phox, Phos, NAG, and urease (p < 0.05), with pronounced increases in Phox (241.13 IU·L−1) and Phos (1126.65 U·L−1), indicating enhanced organic matter mineralization and phosphorus availability. (3) Calcium-driven MBC and ROC accumulation was associated with the positive regulation of Phox (path coefficient > 0.8) and the negative regulation of Phos. SOC was co-regulated by β-glu and Phos (R2 = 0.753). (4) Calcium dynamically optimized the short-term carbon distribution through enzyme activity while promoting long-term sequestration. Our study provides new evidence supporting multi-pathway interactions through which calcium mediates enzyme networks to influence the soil carbon cycle. The findings provide a theoretical foundation for calcium fertilizer management and soil carbon sequestration strategies in agriculture, advancing academic and practical goals for sustainable development and carbon neutrality.